The Influence of Situational Influence, Risk Perception and Advertising Appeal on Purchase Intention During Covid-19 on Tourism Business in Eastern Indonesia - Riesyah Putri Auliyah (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
The Covid-19 pandemic has made Indonesia's tourism business sluggish and less interested. For example, Bali tourist visits as a popular destination decreased by 99.9% (Central Statistics Agency of Bali Province, 2020). Based on Wonderful Indonesia, foreign tourist visits in April 2019-2020 decreased by 87%. A thorough collapse has bankrupted many tourism businesses. Based on this phenomenon, researchers are interested in researching people's interest in carrying out traveling activities, judging from the variables situational influence (Covid-19), risk perception and an advertising appeal. This research is quantitative with population of people who have carried out traveling activities within the last 2 years. The study sample using Non-Purposive Probability totaled 150 respondents. Analysis of the study using multiple linear regression with SPSS software. The results showed that Situational Influence has a positive and significant influence on Purchase Intention. Risk perception has a negative and significant influence on Purchase Intention. Advertising Appeal has a positive and significant influence on Purchase Intention.